2023
DOI: 10.1186/s43058-023-00446-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing provider-led adaptations to mobile phone delivery of the Adolescent Transition Package (ATP) in Kenya using the Framework for Reporting Adaptations and Modifications to Evidence-based Implementation Strategies (FRAME-IS): a mixed methods approach

Abstract: Background The COVID-19 pandemic resulted in disruptions to routine HIV services for youth living with HIV (YLH), provoking rapid adaptation to mitigate interruptions in care. The Adolescent Transition to Adult Care for HIV-infected adolescents (ATTACH) study (NCT03574129) was a hybrid I cluster randomized trial testing the effectiveness of a healthcare worker (HCW)-delivered disclosure and transition intervention — the Adolescent Transition Package (ATP). During the pandemic, HCWs leveraged ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Two previous studies described similar experiences when using the FRAME-IS to document adaptations to multifaceted implementation strategies supporting integration of practice-based interventions. ( 13 , 14 ) For example, Mangale et al( 13 ) found that adaptations to the implementation strategies were not mutually exclusive and fit within several categories resulting in ‘unavoidable overlap.’ Haley et al ( 9 ) also described challenges to tracking adaptations to a multifaceted implementation strategy using existing frameworks. Like our approach, the authors addressed these challenges by adding more detailed information on the changes using the ERIC taxonomy and developed new codes to augment the broad categorization of strategies offered by current frameworks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two previous studies described similar experiences when using the FRAME-IS to document adaptations to multifaceted implementation strategies supporting integration of practice-based interventions. ( 13 , 14 ) For example, Mangale et al( 13 ) found that adaptations to the implementation strategies were not mutually exclusive and fit within several categories resulting in ‘unavoidable overlap.’ Haley et al ( 9 ) also described challenges to tracking adaptations to a multifaceted implementation strategy using existing frameworks. Like our approach, the authors addressed these challenges by adding more detailed information on the changes using the ERIC taxonomy and developed new codes to augment the broad categorization of strategies offered by current frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…A small but growing number of studies have utilized the FRAME-IS to provide important information on the adaptability of various implementation strategies in diverse settings including FQHCs. ( 6 , 13 16 ) However, most of these studies are limited by their focus on a discrete implementation strategy (e.g., training), which do not reflect the complexity of multifaceted strategies such as practice facilitation (PF). To address this limitation, we leverage our ongoing trial, which is evaluating the effectiveness of PF on implementation fidelity of an evidence-based technology facilitated team care model within a large FQHC, to conduct an ancillary study that characterizes adaptations to our implementation strategy using the FRAME-IS.…”
Section: Introductionmentioning
confidence: 99%